Konstruksi Kurikulum dan Pembelajaran Terpadu antara Pendidikan Agama Islam (PAI) dan Pendidikan Kewarganegaraan (PKn) di Sekolah Dasar - Yani, Muhammad Turhan; Setyowat, Rr. Nanik; Islamiyah, Denik Nur; Pranggono, Galeh (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
Model construction of curriculum and integrated learning between the Islamic Religious Education (PAI) and Civic Education (PKn) in elementary schools oriented to synergize the PAI and Civics teachers in designing integrated learning a more comprehensive and effective while improving the personality of students for the future be able to reflect the intellectual potential and the potential for in attitude. Basically, in the process of education and learning , teachers are required to conduct a comprehensive innovations and effective to prevent saturation, both teachers and students. Concerned it, this research produces research that has been tested in three elementary schools (SD) in Surabaya in the form of construction of an integrated curriculum in a way to bring some basic competence of these two subjects, then packaged in an integrated learning syllabus equipped, Learning Implementation Plan, Instructional Materials / Module Simple, and the Learning Guide.